Caribbean Report 19-01-1998 - Ransome, Debbie (anchor); Ramphal, Shridath (interviewee); Gordon, Orin (correspondent); Hoyte, Desmond (interviewee); Forde, Henry (interviewee); Greaves, Keith Stone (correspondent); Gibb, Tom (correspondent); Alarcon, Ricardo (interviewee); de la Vega, Fernando (interviewee); Brabant, Malcolm (correspondent); Chavez, Willie (interviewee) (The British Broadcasting Corporation, 1998)
In Guyana, a CARICOM brokered deal signed by the main political parties agrees to fresh elections by the year 2000 and an independent audit of the elections. However, PNC Leader Desmond Hoyte still calls for fresh polls. Sir Henry Forde comments on what will happen if voting irregularities are found at the heart of the problem. Meanwhile, this accord in Guyana has cleared the way for the cricket test in Georgetown to go ahead. Preparations are in full gear for the third test against England to be held February 17th to March 3rd. In Cuba, the visit of Pope John Paul II has raised many expectations and the suggestion that the visit could bring about major changes. In Florida, the Cuban American exile community is less happy about the papal visit. In Suriname, the government's parliamentary majority has been reduced after three members of the coalition party have defected.
1. Headlines with Debbie Ransome (00:00-00:29)
2. Different views of the Pope's visit from Havana and Miami (00:30-01:05)
3. A CARICOM brokered deal is expected to end Guyana's political woes (01:06-08:23)
4. The third cricket test in the England tour is set to go ahead in Georgetown, Guyana (08:24-09:24)
Keywords: Papal visits -- Cuba; Cooperation -- Caribbean Area; Political stability -- Guyana; Elections -- Corrupt practices -- Guyana; Guyana -- Politics and government; Cricket -- West Indies; Cricket -- Tournaments -- England; Catholic Church -- Cuba; Cuba -- Religious life and customs; Cuban Americans -- Florida -- Miami; Exiles -- Florida -- Miami; Politicians -- Suriname; Suriname -- Politics and government; John Paul II, Pope, 1920-2005 -- Travel -- Cuba